Empirical Evaluation of the Role of African Traditional Religion in Promoting Gender-Based Violence in Southeast Nigeria - Stella C. Ekwueme (Religions)
The tenets and philosophies of the Igbo traditional religion (ATR) form the bedrock of the Igbo traditional and sociocultural belief system whose principles and practices directly and indirectly influence the perceptions and way of life of the Igbo society. These traditional and sociocultural beliefs are practiced in a way that promotes patriarchy, reducing the women to second-class citizens, and often making room for gender-based violence (GBV) against the women. This study is designed to establish the prevalence, forms, effects, and causes of GBV using results from empirical data. A total of 369 women, selected from 12 villages in Enugu State, South Eastern Nigeria, via single-stage adaptive cluster sampling, were involved in the study. The data were analyzed using means, frequencies, and percentages. This study identified a high presence of all forms of physical, sexual, emotional, and economic violence, as well as violence through harmful traditional religious and widowhood practices. More than 70.0% of physical, sexual, emotional, and economic acts of GBV were perpetrated mainly by intimate partners (husbands and/or boyfriends). There was little evidence of intimate partner violence (IPV) in all the forms of harmful traditional and widowhood practices. Rather, traditional and widowhood acts of violence against women are mainly perpetrated by the female peer group (Umuada), family members, and their husbands’ kinsmen (umunna). This study recommends effective outlets for victims to speak out and an action-oriented legal system to bring offenders to justice.